Softball Pitching Propulsion and Performance Differences According to Body Fat Percentage - Friesen, Kenzie B; Oliver, Gretchen D (International Journal of Sports Medicine, 2022)
Softball pitchers with a high body-fat percentage (bf%) can often be successful, despite the heightened risk of injury associated with high bf%. Given the importance of propulsion during pitching, those with high bf% may have an advantage performance-wise. Therefore, the purpose of this study was to examine the differences in ground reaction force (GRF) development between two groups of pitchers: those with a high-fat percentage (≥32 bf%) and a healthy-fat percentage (<32 bf%). Thirty-two female high-school softball pitchers (1.70±.06 m, 76.09±17.50 kg, 15±1 yrs) completed dual-energy x-ray absorptiometry (DEXA) scans. GRF data were collected during pitch propulsion via a force plate, pitch speed was captured using a radar gun, BMI was calculated from pitcher height and mass, and fat free mass index (FFMI) and fat mass index (FMI) were calculated using DEXA data and pitcher height. Multivariate analysis of variance revealed pitcher group GRFs differed significantly (F3,30=3.45, p=.030). Univariate follow-up analyses showed healthy bf% pitchers presented greater weight-normalized peak medial GRF (F1,30=7.17, p=.012). BMI and FFMI were positively associated with pitch speed while bf% and FMI were negatively associated with pitch speed. While pitchers can be successful and carry excess bf%, results indicate potential performance disadvantages associated with having an increased bf%.
Keywords: ball speed; biomechanics; body composition; kinematics; kinetics; performance improvement